Improved prediction of residual stress induced warpage in thermoset composites using a multiscale thermo-viscoelastic processing model. (November 2019) - Chen, Weijia; Zhang, Dianyun
Abstract: A multiscale thermo-viscoelastic processing model is developed to predict the residual stress development in a thermoset composite due to curing. In the proposed modeling framework, a composite laminate is modeled as discrete layers of homogeneous laminae at the macroscale, while at each integration point of the homogeneous model, the constitutive relations of the lamina are determined through micromechanics using an Extended Concentric Cylinder Assemblage (ECCA) model in conjunction with the correspondence principle of viscoelasticity. Since analytical formulations are employed at the microscale, the proposed multiscale approach can efficiently predict the composite time-, temperature-, and cure-dependent responses during processing. The proposed model is employed to predict the warpage shape of an anti-symmetric laminate due to curing-induced residual stresses. Compared with other elastic processing models, the proposed processing model achieves an improved prediction of the warpage shape due to its capability to consider both curing history and stress relaxation during composite processing.